Abuse of Prosecutorial Authority and Ethical Violations in the Robot Trading Fahrenheit Case - Jesslyn Vircilya Chow; Ferisha Iskandar; Jessica Tan; Cornelia Editha Santoso; Chelsea Shine Efendy; Lezhna Nayla Nurjihan; Christine Susanti (Journal of Law, Politic and Humanities, 2026)
Abuse of authority by prosecutors constitutes a form of misconduct that not only violates the law but also undermines the integrity of the prosecution service and public trust in the criminal justice system. This study aims to analyze the forms of abuse of authority and violations of the prosecutorial code of ethics in handling the Robot Trading Fahrenheit criminal case, as well as the legal implications arising from such misconduct. This research employs a normative legal method using statutory and case approaches through the analysis of legislation, the prosecutorial code of ethics, court decisions, and relevant legal literature. The findings show that Prosecutor Azam Akhmad Akhsya abused his authority by exploiting his position for personal gain through the manipulation of law enforcement administration, the creation of fictitious beneficiaries, and the misappropriation of IDR 11.7 billion allocated for the return of seized assets. His conduct fulfilled the elements of corruption under Article 12(e) of the Anti-Corruption Law and violated Attorney General Regulation No. 4 of 2024 concerning the Prosecutors' Code of Conduct. The study concludes that such misconduct gives rise to criminal, ethical, and administrative liability, highlighting the need to strengthen internal oversight and enforcement of the prosecutorial code of ethics to uphold professionalism and institutional accountability.